2014
DOI: 10.1371/journal.pone.0096942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicotine and Porphyromonas gingivalis Lipopolysaccharide on Endothelial Cells In Vitro

Abstract: Smoking is considered a significant risk factor for both periodontal disease and cardiovascular disease (CVD). Endothelial cells play an important role in the progression of both diseases. In the present study, we investigated in vitro the impact of nicotine on functional properties of human umbilical vein endothelial cells (HUVECs) stimulated with lipopolysaccharide (LPS) of periodontal pathogen Porphyromonas gingivalis. HUVECs were stimulated with different concentrations of nicotine (10 µM-10 mM) and/or P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…91 Interestingly, in vitro exposure of endothelial cells to high levels of nicotine (10 mm) resulted in reduced production of the leukocyte chemoattractant, IL-8, and a suppression of endothelial migration in response to stimulation with P. gingivalis-derived LPS. 92 Such evidence is supportive of the anti-angiogenesis hypothesis.…”
Section: The Re S P On S E Of Innate Cell S To Pl Aque In Tobacco Smentioning
confidence: 70%
“…91 Interestingly, in vitro exposure of endothelial cells to high levels of nicotine (10 mm) resulted in reduced production of the leukocyte chemoattractant, IL-8, and a suppression of endothelial migration in response to stimulation with P. gingivalis-derived LPS. 92 Such evidence is supportive of the anti-angiogenesis hypothesis.…”
Section: The Re S P On S E Of Innate Cell S To Pl Aque In Tobacco Smentioning
confidence: 70%
“…Some previous studies showed that EMD stimulates differentiation of osteoblasts grown on moderately rough Ti surfaces 17,19) . One of these studies show that EMD promotes the proliferation and differentiation of osteoblasts an both PT and SLA surfaces, which suggest that the effect of EMD on osteoblasts does not depend on the Ti surface topography 29) .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the angiogenesis related genes intercellular adhesion molecule-1 (ICAM-1), E-selectin, endothelial protein C receptor (EPCR), von Willebrand Factor (vWF), and angopoietin-2 (Ang-2) in HUVECs was measured by quantitative polymerase chain reaction (qPCR) as described previously 13,19) )control. The statistical differences between the effects of the various titanium surfaces on the cultured cells were analyzed by one-way analysis of variance (ANOVA) for repeated measures followed by t-test.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanisms of this relationship have remained obscure. Studies have also indicated that Pg ‐LPS can access systemic circulation and increase the inflammatory response, leading to the breakdown of vascular cells 19 , 20 . In this study, it is identified that Pg ‐LPS is associated with VSMC calcification in vitro, which can further reveal the relationship of periodontal diseases and vascular calcification.…”
Section: Discussionmentioning
confidence: 59%
“…Studies have also indicated that Pg-LPS can access systemic circulation and increase the inflammatory response, leading to the breakdown of vascular cells. 19,20 In this study, it is identified that Pg-LPS is The doses of Pg-LPS investigated (0 to 1,000 ng/mL) were at the low end of the range used in in vitro and in vivo studies (0 to 50,000 ng/mL). 21,22 Dolan et al 23 reported that healthy individuals had blood LPS levels ‡10 pg/mL.…”
Section: Discussionmentioning
confidence: 94%